PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Muhammad Irsyad (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the effect of institutional ownership, managerial ownership and corporate social responsibility on financial performance. The technique used to collect data is documentation technique. The data used in this study is secondary data, namely the company's annual financial statements taken from www.idx.co.id, then the data is selected using purposive sampling method. The population in this study are transportation sub-sector companies for the 2016-2021 period, and the sample used is 10 companies with a total of 60 sample data on the annual financial statements of transportation sub-sector companies. The results of the research conducted using multiple linear regression analysis method, using SPSS 26 software, show that institutional ownership has no significant positive effect on financial performance as measured by returns of no assets. managerial ownership has a significant negative effect on financial performance as measured by return on assets. Corporate social responsibility has a significant positive effect on financial performance as measured by return on assets.